Linezolid Therapy of Staphylococcus aureus Experimental Osteomyelitis - Patel, Robin (American Society for Microbiology, 2000)
The in vivo activity of linezolid or cefazolin against a clinical isolate of methicillin-susceptible Staphylococcus aureus (linezolid MIC, 2 μg/ml) was studied in a rat model of experimental osteomyelitis. Sixty rats with experimental S. aureus osteomyelitis were treated for 21 days with no antimicrobial, with 25 μg of linezolid per kg of body weight administered intraperitoneally twice or three times a day, or with 50 μg of cefazolin per kg administered intramuscularly three times a day. After treatment, the animals were sacrificed and the infected tibiae were processed for quantitative bacterial cultures. The results of treatment were expressed as log(10) CFU/gram of bone and analyzed by rank sum analysis. The results of linezolid treatment were not significantly different from those of untreated controls, while cefazolin treatment was significantly more active than no treatment or linezolid treatment.